Gender-Based Psychosocial Differences in a Sample of Young Offenders - Arteaga, Alfonso (International journal of offender therapy and comparative criminology, 2021)
This study analyzes the differential psychosocial characteristics of male and female young offenders with a judicial measure from a juvenile court in Spain. Data on origin, recidivism, criminal and psychosocial characteristics of a sample of 838 juvenile offenders were collected using the Youth Level of Service/Case Management Inventory (YLS/CMI). Most of the minors were males (n = 650; 77.6%). Regarding the type of offences committed most males committed some type of crime, while females mainly committed misdemeanours. The rates of infractions committed by large groups and belonging to a gang were higher in males than in females. Concerning psychosocial variables, females presented with higher scores than males in three areas (parenting/educational guidelines, leisure and recreation, attitudes and orientation), in the total score and in several specific variables of the YLS/CMI. Moreover, having a poor relationship with one’s mother and limited participation in organized activities were related to being a female minor offender, whereas having a short attention span was related to being a male offender. These three variables correctly classified 77.6% of cases. Female minor offenders present with a more severe psychosocial profile than males. Therefore, gender-based variables should be considered and addressed in prevention and intervention programmes for minors.